Controllable spontaneous resolution in ultrasmall Cu–Ag bimetallic cluster ion pairs from achiral components. Issue 10 (11th January 2022) - He, Jiao; Deng, Cheng-Long; Sun, Cun-Fa; Zhang, Xiao-Xiao; Cui, Ying; Wu, Sheng-Hui; Luo, Geng-Geng
Abstract : Ultrasmall Cu–Ag cluster ion pairs are obtained as conglomerate crystals or racemic crystals through fine-tuning of internal achiral structural components. Abstract : Bimetallic cluster ion pairs containing a quaternary phosphonium and an ultrasmall Cu2 Ag3 anionic cluster protected by thiolates: (PPh3 R′′)[Cu2 Ag3 (SR′)6 ] (R′SH = cyclohexylthiol (CySH), R′′ = Ph, 1 ; Me, 2 ; Et, 3 ; Pr, 4; R′SH = tert -butylthiol ( t BuSH) and R′′ = Ph, 5 ) were reported. Without any chiral source, 1 crystallizes as conglomerate crystals with homochiral packings and spontaneous resolution occurs, while four other clusters 2–5 crystallize as racemic crystals with heterochiral packings. These results indicate that racemic and homochiral crystallization in the cluster system could be controlled through fine-tuning internal achiral structural components.